To solve for x, we can start by isolating the variable terms on one side of the equation.
First, let's subtract 6x from both sides:
(9x + 16) - 6x = (6x + 1) - 6x
This simplifies to:
3x + 16 = 1
Next, let's subtract 16 from both sides:
(3x + 16) - 16 = 1 - 16
This simplifies to:
3x = -15
Finally, we can solve for x by dividing both sides by 3:
(3x)/3 = (-15)/3
This simplifies to:
x = -5
So the solution for x is x = -5.
Solve for x: 9x+16=6x+1.
9 answers
Solve for x: 4x−3=3x−9.
To solve for x, we can start by isolating the variable terms on one side of the equation.
First, let's subtract 3x from both sides:
(4x - 3) - 3x = (3x - 9) - 3x
This simplifies to:
4x - 3 = -9
Next, let's add 3 to both sides:
(4x - 3) + 3 = -9 + 3
This simplifies to:
4x = -6
Finally, we can solve for x by dividing both sides by 4:
(4x)/4 = (-6)/4
This simplifies to:
x = -3/2
So the solution for x is x = -3/2 or x = -1.5.
First, let's subtract 3x from both sides:
(4x - 3) - 3x = (3x - 9) - 3x
This simplifies to:
4x - 3 = -9
Next, let's add 3 to both sides:
(4x - 3) + 3 = -9 + 3
This simplifies to:
4x = -6
Finally, we can solve for x by dividing both sides by 4:
(4x)/4 = (-6)/4
This simplifies to:
x = -3/2
So the solution for x is x = -3/2 or x = -1.5.
Solve for x: 13x+26=3x−34.
To solve for x, we need to isolate the variable terms on one side of the equation.
First, let's subtract 3x from both sides:
(13x + 26) - 3x = (3x - 34) - 3x
This simplifies to:
10x + 26 = -34
Next, let's subtract 26 from both sides:
(10x + 26) - 26 = -34 - 26
This simplifies to:
10x = -60
Finally, we can solve for x by dividing both sides by 10:
(10x)/10 = (-60)/10
This simplifies to:
x = -6
So the solution for x is x = -6.
First, let's subtract 3x from both sides:
(13x + 26) - 3x = (3x - 34) - 3x
This simplifies to:
10x + 26 = -34
Next, let's subtract 26 from both sides:
(10x + 26) - 26 = -34 - 26
This simplifies to:
10x = -60
Finally, we can solve for x by dividing both sides by 10:
(10x)/10 = (-60)/10
This simplifies to:
x = -6
So the solution for x is x = -6.
Solve ax−12=9.
To solve for x, we want to isolate the variable term on one side of the equation.
First, let's add 12 to both sides of the equation:
(ax - 12) + 12 = 9 + 12
This simplifies to:
ax = 21
Next, we can solve for x by dividing both sides by a:
(ax)/a = 21/a
This simplifies to:
x = 21/a
Therefore, the solution for x is x = 21/a.
First, let's add 12 to both sides of the equation:
(ax - 12) + 12 = 9 + 12
This simplifies to:
ax = 21
Next, we can solve for x by dividing both sides by a:
(ax)/a = 21/a
This simplifies to:
x = 21/a
Therefore, the solution for x is x = 21/a.
The area of a rectangle is calculated with the formula A=lw. If the area of a rectangle is 52.5 m2 and the width is 5 m, what is the length? Explain the solution to the real-world problem.(1 point)
Responses
l=10.5
The length is 262.5 m2.
The length is 10.5 m.
The length is 262.5 m.
Responses
l=10.5
The length is 262.5 m2.
The length is 10.5 m.
The length is 262.5 m.
To find the length of the rectangle, we can rearrange the formula for area A = lw to solve for length l.
Given that the area of the rectangle is 52.5 m² and the width is 5 m, we have:
52.5 = l * 5
To isolate the length l, we divide both sides of the equation by 5:
52.5/5 = l
That simplifies to:
l = 10.5
Therefore, the length of the rectangle is 10.5 m.
Given that the area of the rectangle is 52.5 m² and the width is 5 m, we have:
52.5 = l * 5
To isolate the length l, we divide both sides of the equation by 5:
52.5/5 = l
That simplifies to:
l = 10.5
Therefore, the length of the rectangle is 10.5 m.